TRANSFORMATIONAL LEADERSHIP IN INCREASING EMPLOYEE PERFORMANCE PRODUCTIVITY - Abdullah, Abdullah; Holida, Nur (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Leadership styles and models have been widely studied and even used as a characteristic of someone in leading an institution or Islamic boarding school. The purpose of this study is to analyze and understand transformational leadership in building the performance of administrators at the Nurul Jadid Islamic Boarding School, Paiton, Probolinggo, by focusing its study on the Fathimatuzzahro Girls' Dormitory Area. This study used a qualitative approach with an exploratory method to set priorities, develop definitions and determine the final research design. The research results will provide an overview of the importance of a change in organizational culture through transformational leadership so that an organization can survive and be productive at work, as happened in the Fatimatuzzahro' Girls Dormitory Area which is led by the Head of the Region on behalf of Istibsyaroh. Transformational leadership has several characteristics that show the influence of leaders on their subordinates such as inspirational leadership, belief and intellectual stimulation. The author conducted research using qualitative methods with observation techniques, interviews, and documentation. The results of the discussion show that the transformational leadership of the Head of the Female Dormitory Fatimatuzzahro' is very influential on the administrators, and can build and maintain Islamic values